2000
DOI: 10.1034/j.1399-0004.2000.580208.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrachromosomal triplications: molecular cytogenetic and clinical studies

Abstract: A newborn boy had meconium aspiration syndrome, hypospadias, a supernumerary digit on the left hand, hyperbilirubinemia, a fractured right clavicle, osteopenia, liver calcification, and mild pulmonary hyperplasia. Cytogenetic studies showed a chromosome 13 with additional material in 33% of the metaphases. The add(13) was considered to be a probable duplication of 13q12q22. The 13 paint probe hybridized to the add(13) from end to end. Fluorescence in situ hybridization (FISH) studies using retinoblastoma probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 18 publications
5
26
0
Order By: Relevance
“…There are several reports of triplications on chromosomes 2, 5, 7, 9, 10, 13, 15, and 16 [Wang et al, 1999;Reddy and Logan, 2000;Vailard et al, 2003]. To our knowledge, the authors always described an inverted middle repeat, as found in this family.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…There are several reports of triplications on chromosomes 2, 5, 7, 9, 10, 13, 15, and 16 [Wang et al, 1999;Reddy and Logan, 2000;Vailard et al, 2003]. To our knowledge, the authors always described an inverted middle repeat, as found in this family.…”
Section: Discussionmentioning
confidence: 58%
“…The reasons for this mosaicism could be either a primary aberrant zygote with subsequent loss of the aberrant chromosome in a context of ''embryo rescue'' or a postzygotic event. Only one case of a mosaic triplication-13q21q33-has been described [Reddy and Logan, 2000], which was explained most probably by a mitotic event. The same explanation seems to be adequate in this mosaic 12p11.22p12.3 triplication case, which is supported by the molecular analysis of marker D12S1586.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, large inv dup(15) chromosomes are exclusively of maternal origin [Crolla et al, 1995;Huang et al, 1997], and 15q11-q13 duplication associated with a phenotype are generally of maternal origin [Browne et al, 1997;Cook et al, 1997], although a few paternally derived 15q11-q13 duplications associated with severe developmental impairments have also been described [Mohandas et al, 1999;Mao et al, 2000;Veltman et al, 2005;Depienne et al, 2009]. By contrast, 15q11-q13 interstitial triplications are pathogenetic regardless of the origin of the rearranged chromosome 15 [Pettigrew et al, 1987;Clayton-Smith et al, 1993;Holowinsky et al, 1993;Schinzel et al, 1994;Crawford et al, 1995;Cassidy et al, 1996;Chadwick et al, 1996;Long et al, 1998;Reddy and Logan, 2000;Ungaro et al, 2001;Vialard et al, 2003].…”
Section: Introductionmentioning
confidence: 92%
“…Interstitial triplications of 15q11-q13, which result in the tetrasomy of this region, are rare, with only 11 cases reported in the literature [Pettigrew et al, 1987;Clayton-Smith et al, 1993;Holowinsky et al, 1993;Schinzel et al, 1994;Crawford et al, 1995;Cassidy et al, 1996;Chadwick et al, 1996;Long et al, 1998;Reddy and Logan, 2000;Ungaro et al, 2001;Vialard et al, 2003]. Although this small number precludes a precise definition of the associated phenotypes, particularly in cases of paternal origin [Pettigrew et al, 1987;Cassidy et al, 1996;Ungaro et al, 2001], the clinical presentations generally resemble those of patients with tetrasomy of the same region due to an inv dup(15) marker chromosome: normal growth, absent, or very mild craniofacial dysmorphism, hypotonia, epilepsy refractory to therapy, severe to profound intellectual disability (ID), and variable reports of autistic behavior [Robinson et al, 1993;Cheng et al, 1994;Leana-Cox et al,1994;Crolla et al, 1995;Mignon et al, 1996].…”
Section: Introductionmentioning
confidence: 96%
“…14 Triplications are very rare chromosomal rearrangements. 15 In general, the resulting clinical phenotype is consistent with, but more severe than, the duplication of the same locus. 12,14,[16][17][18] Triplications of genomic loci associated with neurocognitive and neuropsychiatric abnormalities have been described, among others, at 22q11.2, 18 7p11.2, 19 Xq28 encompassing the MECP2 gene, 20 and 7q11.23 at the Williams syndrome critical region.…”
Section: Discussionmentioning
confidence: 72%